Isothermal Oxidation Behavior of Aluminized AISI 1020 Steel at the Temperature of 700 oC - Mohammad Badaruddin; Suharno Suharno; Hanif Ari Wijaya (Institute of Research and Community Outreach, Petra Christian University, 2014)
The AISI 1020 steel was coated by dipping it into the molten Al bath at 700 °C for 16s. The coating layer formed on the steel substrate is consisting of Al with a little Fe, FeAl3 and Fe2Al5 layers. The morphologies of the FeAl3 and Fe2Al5 layers are platelet and columnar structures, respectively. The oxidation test was carried out isothermally at 700 °C for a various time of 1-49 h in static air. The oxidation behaviors of both of the bare steel and the aluminized steel were studied by the oxidation kinetics, surface morphologies and phase transformation after oxidation testing. The oxidation products were characterized using Optical Microscope (OM), Scanning Electron Microscopy with Electron Dispersive Spectroscopy (SEM/EDS) and X-ray diffraction analysis. The magnitude of the rate constant (kp) of the aluminized steel is two order lower than the bare steel. The formations of intermetallic phases on the steel substrate for a shorter time are dominated by the interdiffusion between the inward diffusion of Al-atoms into the steel substrate and outward diffusion of Fe-atoms. The constituent phases in the aluminide layer compose of FeAl2, Fe2Al5 and FeAl. The formation ofFeAlphase is controlled by the inward diffusion of Fe-atoms into the Fe2Al5 phase. The improvement of the oxidation resistance of the aluminized steel subjected to severe oxidation is due to the formation of protective Al2O3scale.